(untitled) (Emancipação, 2026)
This article presents the trajectory of the Brazilian Student Assistance, focusing on the National Program of Student Assistance (PNAES), which was the first legal instrument to regulate Student Assistance in higher education, guiding the formulation and implementation of this policy in federal universities in the last 17 years. In this essay, we aim to understand the contradictory relations surrounding the PNAES, highlighting how they have been manifested in the latest stage of Brazilian capitalism, characterized by the ultra-neoliberalism, the expropriation of rights, and the reinvigoration of conservatism. For this purpose, a bibliographical and documentary research was conducted, considering the PNAES and the Program of Student Assistance at the Federal University of Paraíba (UFPB) from 2015 to 2022. Through the research, we identified how the UFPB students access the Student Assistance Program and the types of challenges that have arisen for this policy to take root in the federal universities as a policy of law.